2008
DOI: 10.21236/ada488140
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Seismic Noise and it's Relevance to Personnel Detection

Abstract: Seismic noise refers to the ambient ground motion within which signals of interest are to be detected. Four categories of seismic noise identified by source-road (vehicle), train, wind, and ocean microseisms-are reviewed. Examples are given of the variation in seismic noise by geographic location and by season and time of day, and of a technique to characterize seismic site effects from local seismic noise. Noise impact on seismic detection of personnel is discussed, and ground motion induced by a walking pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Ambient vibrations Ambient noise of anthropic and meteorological origin had been known since long time to affect the frequency band above 1 Hz, where the main vibration modes of historical buildings generally fall. Meteorological perturbations also increase ambient noise at low frequencies (f <1 Hz) [Longuet-Higgins 1950, Bonnefoy-Claudet et al 2006, Peck 2008, Vassallo et al 2012. In particular, Withers et al [1996] demonstrated that there is a strong correlation between wind speed and seismic background noise at seismological stations installed both in free-field and in bore-hole at different depths; they found that wind speed has a significant role in increasing seismic noise amplitude, especially at the surface, when it exceeds a threshold value of about 10 km/h.…”
Section: Column Imentioning
confidence: 99%
“…Ambient vibrations Ambient noise of anthropic and meteorological origin had been known since long time to affect the frequency band above 1 Hz, where the main vibration modes of historical buildings generally fall. Meteorological perturbations also increase ambient noise at low frequencies (f <1 Hz) [Longuet-Higgins 1950, Bonnefoy-Claudet et al 2006, Peck 2008, Vassallo et al 2012. In particular, Withers et al [1996] demonstrated that there is a strong correlation between wind speed and seismic background noise at seismological stations installed both in free-field and in bore-hole at different depths; they found that wind speed has a significant role in increasing seismic noise amplitude, especially at the surface, when it exceeds a threshold value of about 10 km/h.…”
Section: Column Imentioning
confidence: 99%
“…It should be noted that both signals and noise are measured at the seismic stations and therefore the duration-amplitudes include both as well. (For a discussion of seismic noise and spectra see Peterson (1993) and Peck (2008).) From this point on, the paper uses exponential fits of the data and time windows that match the length of the activity from seismograms.…”
Section: Duration-amplitude Plotsmentioning
confidence: 99%
“…잡음은 사람이 인공적으로 만든 것에서 발생하는 인공적인 잡음(culture noise)과 자연환경에서 발생하 는 자연 발생적인 잡음(natural noise)으로 구분할 수 있다. 환경 잡음 중 진동 시스템에 가장 영향을 많이 주는 것이 도로(차량) 잡음과 바람 잡음이다 [8] . 진동 센서를 설치시, 잡음원(noise source)을 구체적으로 파 악해야 하고, 설치하는 위치와 시설도 정확히 분석해 야 한다.…”
unclassified